INTEGRATING ONLINE AND OFFLINE LEARNING IN ENTREPRENEURSHIP EDUCATION: AI’S ROLE IN REDUCING REGIONAL DISPARITIES - Husein, Muhammad Ahmi; Araminta, Lavinia Disa Winona; Syahrir, Nur Hilal Andi (Jurnal Pendidikan Ilmu Sosial, 2025)
This study aims to describe the impact of learning methods in online and offline entrepreneurship learning for Indonesian students with the constraint of regional disparities in accessing learning. Many online learning platforms have been widely used in recent years due to its benefits such as flexibility and accessibility. However, offline learning is more preferable for hands on skills development in entrepreneurship learning. In this study, we use quantitative methods approach by applying Chi-Square Analysis and the Wilcoxon SignedRank Test to analyse the data of the experiment which has been conducted by collecting the data of 172 students in 4 development regions of Indonesia. Although the learning methods in online have been increasingly popular, the result of this study shows that most of the students more prefer offline learning methods because of its interactive and hands on experience. The result of this study can be a reference for policymakers and educational institutes about the importance of both learning methods even how we can overcome the problem of connectivity in offline learning in various regions so that the entrepreneurial learning can be equally accessed by Indonesian students. In addition, this study also discusses the opportunity of Generative Artificial Intelligence (Gen-AI) in entrepreneurship education for achieving the learning environment which is inclusive and promote equality among students.